The use of whole-body vibration as a golf warm-up - Bunker, D. J.; Matthew, R.; Simons, T.; Marin, P. J. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this case series was to test the effectiveness of an active warm-up for recreational golfers using a whole-body vibration (WBV) platform. The variables that the warm-up tested for were increased flexibility, power, and golf performance. Ten adult men (age: 45 ± 15 yr) volunteered to perform their personal warm-up and record 7 of their golf swings. They then participated in an active warm-up involving flexibility exercises on the iTonic WBV platform and then recorded 7 more golf swings. The settings for the iTonic WBV platform were set to a frequency of 50 Hz and an amplitude of 2 mm, and each exercise was performed for 30 seconds. Eight different exercises were used for this warm-up. Significant changes (p < 0.05) were measured after the WBV warm-up in the following variables: sit and reach, ball speed, carry distance, and total distance. In a subgroup of subjects less than 45 years of age (n = 5), results mimicked those reported for the entire group in that both flexibility and power measures improved significantly. Subjects older than 45 years (n = 5) did not significantly (p < 0.05) improve in power measures but did improve sit and reach similarly to the younger group. These data suggest that a profound increase in the flexibility and power output of individual golfers occurs when a WBV warm-up bout is performed.